Executing Crisis : Your C-Suite Crisis Leadership Survival Guide. - Roberson, Jo (Rothstein Associates, Incorporated, 2019)
Business leaders would be better served by understanding key crisis concepts and applying them to their own situation rather than relying on crisis advisors to swoop in to take care of a problem once it has become a crisis. Loaded with Case Studies! How leaders deal with crisis can clarify character and strengthen reputation. On the other hand, the wrong words and actions from the C-Suite can worsen the crisis spiral. Crisis management does not begin on the day the fire erupts, the hurricane barrels through, or the accident happens. Dr. Jo Robertson, a leading expert in heading off and containi.